Effects of glazes on the keeping quality of bread - Abdullah, Rohaiza (2010)
This work describes a study on the effects of different glazes on the keeping quality of bread in term of its crumb and crust properties. Four types of glazes which are corn starch, egg white, skim milk and shortening with four concentrations, i.e., 20%, 30%, 50% and 70% were applied on sweet bun surfaces to determine their effect on staling during six days of storage.